Daylight, Definition, Interpretation and Application Today - Aleksandar, Radevski; Karanakov, Bojan; Papasterevski, Dimitar (Scientific Foundation SPIROSKI, 2022)
Light is a universal medium that illuminates our world. It is the key to discovering the mysteries of the universe, of the spiritual and physical dimensions of the human past, present and future. The history of light and its impact on our world is almost infinite, and through it we search for the origin of life and civilization. It is a story that starts with the beginning of the world and goes on all the way to the development of quantum physics. It unifies and intertwines the art, science, architecture, religion, and philosophy in time and space.
Keywords: Light; Visual perception; History of lighting